2014
DOI: 10.2337/db14-0991
|View full text |Cite
|
Sign up to set email alerts
|

Unacylated Ghrelin Induces Oxidative Stress Resistance in a Glucose Intolerance and Peripheral Artery Disease Mouse Model by Restoring Endothelial Cell miR-126 Expression

Abstract: Reactive oxygen species (ROS) are crucial in longterm diabetes complications, including peripheral artery disease (PAD). In this study, we have investigated the potential clinical impact of unacylated ghrelin (UnAG) in a glucose intolerance and PAD mouse model. We demonstrate that UnAG is able to protect skeletal muscle and endothelial cells (ECs) from ROS imbalance in hind limb ischemiasubjected ob/ob mice. This effect translates into reductions in hind limb functional impairment. We show that UnAG rescues si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
74
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(78 citation statements)
references
References 50 publications
(91 reference statements)
4
74
0
Order By: Relevance
“…The results show that UnAG negatively regulates skeletal muscle ROS production and inflammation, and these effects are indirectly supported by previous in vitro observations in nonmuscle cells (14,16,19). In another study, UnAG reduced endothelial oxidative stress in models of peripheral artery disease by restoring SOD expression (15,16). Skeletal muscle SOD expression and antioxidant enzyme activities were, however, unchanged by UnAG in the current model, indicating lower mitochondrial ROS generation rather than enhanced antioxidant defenses as a key mediator of UnAG-induced muscle antioxidant activity.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The results show that UnAG negatively regulates skeletal muscle ROS production and inflammation, and these effects are indirectly supported by previous in vitro observations in nonmuscle cells (14,16,19). In another study, UnAG reduced endothelial oxidative stress in models of peripheral artery disease by restoring SOD expression (15,16). Skeletal muscle SOD expression and antioxidant enzyme activities were, however, unchanged by UnAG in the current model, indicating lower mitochondrial ROS generation rather than enhanced antioxidant defenses as a key mediator of UnAG-induced muscle antioxidant activity.…”
Section: Discussionsupporting
confidence: 88%
“…Finally, UnAG effects in vitro are abolished by autophagy inhibition, thereby indicating mechanistic involvement of autophagy in UnAG activities. The results show that UnAG negatively regulates skeletal muscle ROS production and inflammation, and these effects are indirectly supported by previous in vitro observations in nonmuscle cells (14,16,19). In another study, UnAG reduced endothelial oxidative stress in models of peripheral artery disease by restoring SOD expression (15,16).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In ob/ob mice, antioxidant treatment induces a miR-126-dependent anti-inflammatory and antioxidant vascular response [98], an effect also observed in HUVEC [99]. Both miRNAs, miR-21 and miR-126, are upregulated by unidirectional shear stress, protecting EC from apoptosis and increasing the activation of eNOS [100].…”
Section: Potential Role Of Hypoxia-induced Mirnas Mir-21 and Mir-126mentioning
confidence: 89%
“…The activity of SIRT1 has been shown to be rescued by several compounds, such as resveratrol (D'Onofrio et al 2015;Sanchez-Fidalgo 2012), unacylated ghrelin (D'Onofrio et al 2015;Togliatto et al 2014), and ginsenoside Rb1 (D'Onofrio et al 2015;Song et al 2014), a steroid glycoside found in ginseng and paeonol (D'Onofrio et al 2015;Jamal et al 2014). Resveratrol, a polyphenolic antioxidant found in red wine, activating SIRT1 (Villalba and Alcain 2012;Wallerath et al 2002) prevents oxidative stress and coronary VSMC proliferation inhibiting extracellular signal regulated kinase (ERK) activation (Chong et al 2012;El-Mowafy et al 2008).…”
Section: The Sirtuin Familymentioning
confidence: 99%